VALIDATION ANALYSIS OF CONTEXTUAL-BASED COMIC LEARNING MEDIA DEVELOPMENT ON TORQUE CONCEPT MATERIALS IN SMA (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2021)
Lack of student interest in studying physics because in addition to lessons that are considered difficult, learning media are also still less attractive so that learning media are needed that can make students interested in a pleasant learning atmosphere that is supported by learning that connects material with applications that occur in everyday life such as contextual based physics comics. The purpose of this research is to produce a product in the form of contextual-based comic media on torsional concept material in high school. The analytical technique used is descriptive qualitative analysis to be able to describe the validation of the questionnaire from the validators of material experts and media experts. This study uses Research and Development (R&D) research with a 4-D model consisting of define, design, development, and dissemination stages. The research is limited due to time constraints so that it only reaches the development stage. The results of the study obtained a material validity value of 4.05 or 81% which was included in the very feasible category and the media validity value of 4.5 or 90% which was included in the very feasible category. From the results of the study, it can be concluded that the development of contextual-based comic learning media on torsional concept material in high school is very feasible to be used as a learning resource. Keywords: Validation, learning media, comic, and contextual